2017
DOI: 10.1136/emermed-2017-206584
|View full text |Cite
|
Sign up to set email alerts
|

Perceived support at work after critical incidents and its relation to psychological distress: a survey among prehospital providers

Abstract: Prehospital providers at risk of psychological distress may benefit from support from colleagues and management and from having time to recover after critical incidents. Formal peer support may assist providers by increasing their sense of support from colleagues. These findings need to be verified in a longitudinal design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…well-being (Gouweloos-Trines et al, 2017;Revicki & Gershon, 1996;Shakespeare-Finch & Daley, 2017;Sterud, Hem, Ekeberg, & Lau, 2008;van der Ploeg & Kleber, 2003). The current study is distinct in that the measure of social support used here reflects personal relationships and interactions outside the workplace.…”
Section: Discussionmentioning
confidence: 97%
“…well-being (Gouweloos-Trines et al, 2017;Revicki & Gershon, 1996;Shakespeare-Finch & Daley, 2017;Sterud, Hem, Ekeberg, & Lau, 2008;van der Ploeg & Kleber, 2003). The current study is distinct in that the measure of social support used here reflects personal relationships and interactions outside the workplace.…”
Section: Discussionmentioning
confidence: 97%
“…Some paramedics experience lengthy offload delays which render them unable to talk privately after the call as they are caring for patients in hospital hallways. Nearly 60% of paramedics surveyed (N=813) from eight Western countries said they lacked time to talk after CIs, which resulted in higher distress levels than among paramedics who felt they had adequate time (47). A previous study identified that a 30 to 60 minute break after CIs is important to paramedics and when they receive downtime after calls, rates of depression are reduced (25).…”
Section: Discussionmentioning
confidence: 99%
“…Patient death, uncertainty, managing distressed family members and witnessing acute grief reactions have all been identified as potential workplace stressors for ambulance personnel (54,55). The strategies identified in this review, including downtime (56), peer support (12,55) and the use of emotional detachment (57,58) have all previously been identified as key coping mechanisms for emergency personnel managing critical incidents. Without adequate preparation and support, it appears some ambulance personnel distance themselves from decision-making and commence or continue resuscitation in order to avoid managing a patient death and engaging with the grief of bereaved family members.…”
Section: Discussionmentioning
confidence: 96%